Apparatus for exposing cell membranes to rapid temperature transients. - Steel, B; Bilek, M; dos Remedios, C; McKenzie, DR (2004)
We seek to determine whether cell membranes contain sensors that trigger a downstream response to temperature excursions. To do this, we have developed a novel apparatus for exposing a cell membrane to an extremely rapid temperature excursion in the nanosecond range. Cells are plated on a gold surface that is back-heated by a pulsed laser and cooled by conduction of heat into the glass substrate and the liquid medium. Analysis using the heat diffusion equation shows that the greatest temperature rise is localized within a region tens of nanometres thick, suitable for specifically heating a cell membrane without heating the remainder of a cell. We refer to this device as a nanosecond hotplate.